The Effectiveness of Group Marital Conflict Resolution Training Based on Choice Theory on Emotional Divorce and Hope for Life in Married Women - Abedi, Ghodrat; Ataeifar, Robabeh; Ghamari, Mohammad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The primary objective of this study was to examine the effectiveness of group marital conflict resolution training based on Choice Theory on emotional divorce and hope for life among married women in 2023. Methods and Materials: A quasi-experimental research design was used, with a sample of 50 married women selected via convenience sampling from counseling centers in Alborz Province, Iran. Participants were randomly assigned to experimental (n = 25) and control (n = 25) groups. The experimental group received group training based on Choice Theory over 9 sessions, while the control group received no intervention. Data were collected using Gottman’s Emotional Divorce Questionnaire (1997) and Snyder’s Hope Scale (1991), administered during pre-test, post-test, and follow-up phases. Data were analyzed using descriptive statistics and multivariate analysis of covariance (MANCOVA). Findings: The results indicated a significant negative effect of Choice Theory-based marital conflict resolution training on emotional divorce and a significant positive effect on hope for life (p < 0.05). Specifically, the training led to significant reductions in two components of emotional divorce—need for attention and affection, and need for belonging—while no significant changes were observed in feelings of loneliness and restlessness. Regarding hope for life, the training significantly improved the strategic thinking component, but no significant effect was found for the agency thinking component. Conclusion: Group marital conflict resolution training based on Choice Theory effectively reduces emotional divorce and increases hope for life among married women.